Evaluation of fresh frozen plasma usage at the University Hospital Center Rijeka - Balen, Sanja, liječnica; Caser, Linda; Ivanković, Edita; Samardžija, Marina; Ivanković, Josip, liječnik; Včev, Aleksandar (2009)
Abstract: The aim of this investigation was to assess the rate and appropriate use of fresh frozen plasma (FFP) at the Clinical Hospital Center Rijeka in two six-month periods, at an interval of 5 years, before and after introducing clinical standards for transfusion practice and hemovigilance, and to evaluate the results of applied measures. We studied 315 patients transfused with 1341 doses of FFP in two six-month periods from September to February of 1999/2000 and 2004/2005. The first period (1999/00) of the study was retrospective and 226 patients were transfused with 928 FFP units. The second period (2004/05) was prospective and we studied 89 patients transfused with 413 units. In the first period blood bank records were retrospectively reviewed and in the second period all FFP requests, performed coagulation tests and transfusion episodes were prospectively analyzed. The number of inappropriate transfusions decreased from 39.8% to 23.6%. In most patients (85.1%), coagulation tests were made prior to FFP transfusion. The number of patients transfused with one and two FFP doses decreased, while those transfused with three or more doses increased. Most of the appropriately transfused patients were those with active bleeding due to coagulation factor deficiency and massive transfusions. The least were those requiring reversal of warfarin effect. Our results demonstrated a decrease in the number of patients treated with FFP in the second period. The introduction of clinical standards of good transfusion practice and hemovigilance showed positive effects. Considering that there was a number of inappropriately transfused patients continued education of all health personnel engaged in transfusion treatment is evidently necessary
Bibliografija: 40 jed
Sažetak
Keywords: Svježe smrznuta plazma -- Transfuzijsko liječenje; Kliničko bolnički centar Rijeka